2020
DOI: 10.1186/s13068-020-01746-4
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline organosolv pretreatment of different sorghum stem parts for enhancing the total reducing sugar yields and p-coumaric acid release

Abstract: Background: The sorghum stem can be divided into the pith and rind parts with obvious differences in cell type and chemical composition, thus arising the different recalcitrance to enzyme hydrolysis and demand for different pretreatment conditions. The introduction of organic solvents in the pretreatment can reduce over-degradation of cellulose and hemicellulose, but significance of organic solvent addition in pretreatment of different parts of sorghum stem is still unclear. Valorization of each component is c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In the present study, the morphology of SBB was significantly changed after combined pretreatment when compared to raw SBB. Similar results were also observed in a previous study reported by Li et al ( 2020 ). This morphological change is caused by the saponification reaction between NaOH and the intermolecular ester bond of lignin, which results in the removal of the surface lignin layer and the release of cellulose from the biomass matrix, exposing more of the internal structure and increasing the external area (Umagiliyage et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the morphology of SBB was significantly changed after combined pretreatment when compared to raw SBB. Similar results were also observed in a previous study reported by Li et al ( 2020 ). This morphological change is caused by the saponification reaction between NaOH and the intermolecular ester bond of lignin, which results in the removal of the surface lignin layer and the release of cellulose from the biomass matrix, exposing more of the internal structure and increasing the external area (Umagiliyage et al, 2015 ).…”
Section: Resultssupporting
confidence: 93%
“…5‑1h , S A1‑1h , and S A2–1h , dense holes and broken surfaces are noticed. Indeed, due to the removal of a large amount of lignin, alkali-catalyzed pretreatment results in structural changes on the biomass surface that facilitates enzyme erosion. , …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, due to the removal of a large amount of lignin, alkali-catalyzed pretreatment results in structural changes on the biomass surface that facilitates enzyme erosion. 40,41 3.2.4. Enzymatic Hydrolysis.…”
Section: Sem Analysismentioning
confidence: 99%
“…This requires innovation in technologies and the complete valorization of various feedstocks in an environmentally friendly manner. Biorefinery is of great importance for alleviating the shortage of industrial raw materials, and the overreliance on fossil resources as biomass resources are renewable, cheap, and widely accessible. Lignocellulosic biomass, mainly consisting of cellulose (∼40%), hemicellulose (∼20%), and lignin (∼20%), is the most abundant biomass feedstock that can be converted to various products such as building materials, papers, biofuels, and biochemicals. However, most conventional biorefining processes such as pulping and bioethanol industries focus on the use of carbohydrates (i.e., cellulose and hemicellulose). In contrast, lignin, a natural aromatic polymer, and one of the most attractive renewable precursors for smart material preparation, is not fully utilized. Taking the bioethanol industry as an example, by 2022, about 62 million tons of lignin are predicted to be produced annually in the United States, and an increasing amount of extra lignin will be left after providing external energy by combustion. ,, Valorizing lignin is meant to enhance the profitability of conventional biofuel and biochemical scenarios, thus enhancing the economy of biorefining …”
Section: Introductionmentioning
confidence: 99%